GUIDELINES ON AUTHENTIC ASSESSMENT PROMOTION FOR ENGLISH LANGUAGE TEACHERS IN SCHOOLS UNDER NAKHONNAYOK PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Charuchinda, Intira; Supawan, Pornsin (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
This research aimed to: 1) study the condition, problems, and need for training in authentic assessment of English language teachers under the Nakhonnayok Primary Educational Service Area Office, and 2) develop guidelines on authentic assessment promotion. This study consisted of two phases. The first phase was to investigate the condition, problems, and need for training in authentic assessment. The population was 145 teachers and five key informants. The research instruments were a questionnaire and a semi-structured interview form. The data were analyzed using descriptive statistics, namely frequency, percentage, mean, and standard deviation. Also, content analysis was performed. The second phase was to propose guidelines on authentic assessment promotion for English language teachers in these schools, which had been validated by six experts in English language teaching. The findings revealed the following: 1) The teachers used at least one type of authentic assessment. The most frequently used one was worksheet assignment, followed by observation. The least frequently used ones were project work, exhibition, and presentation. Moreover, the teacher’s attitudes, knowledge, and implementation were at high levels. The problems with the implementation of authentic assessment arose from students, students’ families, classroom contexts, budgeting, and teachers. The teachers expressed their need for training in other topics more than theirs in authentic assessment. They would prefer a blended learning model. 2) The guidelines for authentic assessment promotion proposed by the researchers covered four aspects: (1) teachers; (2) a training model; (3) school administrators’ support; and (4) policies of the Ministry of Education.